Analisis Konsep Biaya dalam Manajemen Rumah Sakit: Tinjauan Efisiensi dan Pengendalian Keuangan - Duratul Fahlia; Yuri Sadewo; Desi Komalasari; Budi Hartono (MES Bogor, 2026)
Hospitals as healthcare service institutions have a high level of complexity in financial management, especially in the era of the National Health Insurance (JKN) with the INA-CBGs payment system. The concept of cost becomes an essential element in supporting operational efficiency and financial control in hospitals. This study aims to analyze the application of cost concepts in hospital management and their role in improving efficiency and financial control. The method used is descriptive research with a literature study approach. Data were obtained from scientific journals, textbooks, and reports related to hospital management. The results show that the application of cost concepts such as fixed costs, variable costs, and unit cost plays a significant role in improving operational efficiency and supporting budget control. In addition, the use of the Activity Based Costing (ABC) method provides a more accurate cost description. The conclusion of this study is that a proper understanding and implementation of cost concepts can sustainably improve the financial performance of hospitals.